Studies on the effect of 4-hydroxy-4-phenylpiperidine derivative (4HPPD) on mice brain serotonin levels - Helal Uddin, A.B.M.; Saeed, Mohammad (International Islamic University Malaysia, 2005)
Synthetic derivative of 4-hydroxy-4-phenylpiperidi ne (4HPPD) given intraperitoneally to male mice increased brain 5-HT levels in 1 hr. T he increase caused by the synthetic derivative was greater than that of pethidine.